Pengaruh Audit Tenure, Ukuran KAP, Pergantian Auditor, Dan Opini Audit Terhadap Audit Delay - Cahyo Prasetyo; Crish Kuntadi (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to analyze the influence of audit tenure, KAP size, auditor changes, and audit opinion on audit delay. Audit delay is the time span for completing a financial report audit by an independent auditor, which can affect the timeliness of submitting financial reports. Audit tenure, KAP size, change of auditors, and audit opinion are considered as factors that can influence the length of audit delay. This research uses data from audit reports of companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. Data analysis was carried out using multiple linear regression. The research results show that audit tenure and change of auditors have a positive effect on audit delay, while KAP size and audit opinion have a negative effect. These findings provide implications for regulators and the audit profession to establish appropriate policies regarding audit tenure, changing auditors, and selecting appropriate KAPs to minimize audit delays and increase the timeliness of financial reporting.